Effectiveness of Nurse Led Education Program on Knowledge regarding Human Milk Banking among Antenatal Mothers Admitted in Selected Hospital of Man galuru, India - Veenith, Divya; Augustin, Bibi (Annapurna Journal of Health Sciences, 2025)
Introduction: A Human milk banking is essential for the health of premature and sick infants. Educating antenatal mothers about this practice can increase awareness and encourage milk donation. Nurses as trusted healthcare providers, are well suited to lead these education programs in mangaluru. Methods: A quasi-experimental two-group pre- and post-test design with an evaluative approach was adopted to assess the knowledge of 80 antenatal mothers in their third trimester selected by convenient sampling techniques from a hospital in Mangaluru. The information required were collected using socio-demographic sheets knowledge ascertained by structured questionnaire consisting of 20 questions were used. Data was used to summarized and evaluated by descriptive and inferential statistics. Results: Pre-test and post-test mean score of the experimental group the pre-test knowledge score was 9.23±1.49 and post-test was 16.23± 1.35 with the gained percentage 21.33% which is statistically very highly significant with computed ‘p’value of 0.001. Whereas in control group mean pre-test knowledge score was 8.75± 2.05and mean post-test was 7.73± 1.68 with ‘p’ value 0.051 showing there was no statistically significant difference between pre-test and post- test knowledge scores, with mean percentage gain of 2.01% . Overall knowledge score between experimental and control group calculated using unpaired “t” test and was statistically significant at 0.05 level. There was significant association between pre-test knowledge score and gestational age. Conclusion: The intended nurse led education program can bring significant improvement among antenatal mothers and suggested that further evidence-based research should be conducted to improving maternal and child health outcomes related to human milk bankin